ANALISIS MODEL PROJECT BASED LEARNING DALAM PEMBELAJARAN TEMATIK INTEGRATIF KELAS IV SD NEGERI PRINGANOM 1 KECAMATAN MASARAN KABUPATEN SRAGEN TAHUN PELAJARAN 2020/2021 - Anisa Putri; Anita Trisiana; Oktiana Handini (UNIVERSITAS SLAMET RIYADI, 2022)
The purpose of this study was to analyze the use of the Project based learning model in integrative thematic learning and find out the impact that occurs on the use of the Project based learning model in integrative thematic learning for fourth grade students of SD Negeri Pringanom 1, Masaran District, Sragen Regency. The research method used is descriptive qualitative research. The subjects of this study were fourth grade students, class teachers and school principals at SDN Pringanom 1, Masaran District, Sragen Regency. Data collection methods in this study are observation, interviews, and documentation. Interviews are used to obtain the information needed in research. Documentation is used to find out school profiles, learning materials for lesson plans and syllabus, data on fourth grade students at SDN Pringanom 1 for the 2019/2020 academic year, photos of media posters produced by students. Data collection techniques used are observation, interviews and documentation. The results of the research that has been done, the use of the Project Based Learning learning model has an impact that the teacher faces. The impact of using the project based learning model is in managing time, the teacher has difficulty managing learning time because the completion of posters carried out by students exceeds sufficient time duration long and need to be limited. Keywords: Learning model, Project Based Learning, Integrative Thematic.